Nasopharyngeal carcinoma and Dermatomyositis: a case report - C. Botsios; P. Boscolo Rizzo; M.C. Da Mosto; P. Ostuni; P. Sfriso; S. Todesco; C. Marchiori (Reumatismo, 2002)
Nasopharyngeal carcinoma has long been reported as the predominant type of cancer associated with dermatomyositis in many several Asian countries, including Hong Kong, Singapore, and Southern-Cina. Dermatomyositis is one of the idiopathic inflammatory myopathies showing characteristic cutaneous manifestations. Reviews from the western literature have demonstrated that certain cancers, such as ovarian and breast carcinoma in women and lung and prostate carcinoma in men, are highly associated with DM relative to the general population. We report the case of a Caucasian Italian patient with nasopharyngeal carcinoma and dermatomyositis. Considering the rarity of nasopharyngeal carcinoma among whites, both the detection and the report of each new case are noteworthy in defining the geographic and ethnic distribution of this tumor.